The life cycle carbon balance of selective logging in tropical forests of Costa Rica - Alice-Guier, Federico E. (2020)
Se seleccionó la licencia Creative Commons para este envío. El documento trae lo siguiente: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited. c 2019 The Authors. Journal of Industrial Ecology, published by Wiley Periodicals, Inc. on behalf of Yale University